The The Digitization of Latin American Immigrant Enterprises in Chile (2020-2022) - Ramírez, Catalina Marcela (2025)
The digital platform economy is transforming the nature of work. Alongside the large companies that promote change, there are precarious subordinate groups that reinforce the restructuring. One of these was the Latin American women of the Migrant Woman Entrepreneur: Collaborative Growth Community (MWECGC) program in Chile. Therefore, the general objective of the research is to analyze the mode of insertion of these women into the digital economy of Chile and to elucidate the labor profile of the group before and after their arrival in the country. Starting from the hypothesis that the crossing of individual biographies with the socio-economic context are fundamental for the development of the enterprise, a Netnography was carried out with 49 women who participated in the project. The results show that the confluence of individual and contextual factors produced four types of female entrepreneurs. The conclusions suggest that the digitization of entrepreneurship does not guarantee its visibility and reach, relativizing the supposed democratizing potential of the platforms.